Effect of flipped classroom model on academic achievement, academic satisfaction and general belongingness - Polat, Hakan; Karabatak, Songul (Springernature, 2022)
The effect of the flipped classroom model on students' academic achievement, academic satisfaction, and general belongingness was investigated using an experimental design. Purposive sampling was used to select 94 undergraduate students as participants. The participants were divided into three groups: one experimental group with the flipped classroom model and two control groups with the traditional classroom and distance education models. The groups attended the same course content sessions that are suitable for their classroom model over eight weeks. For analysis, descriptive statistics, dependent groups t-tests, Wilcoxon signed-rank test, ANCOVA, and ANOVA tests were performed. Students' academic achievement, academic satisfaction, and general belongingness levels significantly increased in the flipped classroom compared with the other classroom models. Suggestions for future research and limitations of the study are provided.
Keywords: Academic achievement; Academic satisfaction; Distance education; Flipped classroom; General belongingness; Traditional classroom